The Two Lives of a Teacher - Gudeliauskė, Gintarė; Rutkienė, Aušra; Tandzegolskienė-Bielaglovė, Ilona (Pedagogika, 2025)
In the article the conception of the intellectual humility of a teacher is revealed when a condition of a dialogue is realized while creating a carnival atmosphere (Bakhtin, 1981; 1984a; 1984b) and searching for potential possibilities to analyse (self-)liberation situations in learning. During the research, the access to critical ethnography has been used, applying critical discourse analysis for data analysis: triadic structure (Fairclough, 2015), revealing the choice of a teacher of two lives, which slows down the process of learning, losing a possibility to grow as a professional. The completed research shows that a teacher, even though he/she admits that he/she does not have to know everything, there are situations when the assumed behaviour of knowing everything is tried to be chosen (aiming for monologism). It does not match with the conception of an intellectually humble teacher (aiming for dialogism). It is worth noting that a teacher can be open to others and, in this way, participate in a dialogue and reconsider his/her beliefs, aiming to find out new aspects. In the interaction with the School Principal, the situations of balancing between behaviour marked with intellectual humility and accepting an indulging position occur. It can be stated that the choice of the two lives of a teacher slows down learning progress.